Development of Gamification-Based Wordwall Game Platform on Reaction Rate Materials - Rokhim, Deni Ainur; Agustina, Nur Indah; Munzil, Munzil (Orbital: The Electronic Journal of Chemistry, 2022)
The purpose of this study was (1) to determine the development of a wordwall game platform on the reaction rate material, (2) to determine the feasibility of a gameification-based wordwall game platform from the results of validator and respondent data. wordwall is an application that can be used as a learning media, learning resource or online-based assessment tool that is attractive to students. The advantage of this application is that it has many templates that teachers can create to develop in the form of games. Wordwall is rarely used in learning media because there has not been socialization and application in the teaching and learning process for teachers. In this study, media development was carried out using wordwall applications on chemicals, namely the reaction rate that will be studied by students. This material contains the concept of reaction rate, factors that affect reaction rate, collision theory and reaction rate equations. The novelty of this study compared to existing research is that this research develops a wordwall medium that focuses on increasing students' interest in learning materials, especially chemistry in the online-based teaching and learning process.The wordwall media validators were 2 lecturers from Nusa Cendana University and the question validators were validated by 2 teachers at SMAN 3 Sidoarjo. The trial subjects were 37 students of high school class XI at SMAN 3 Sidoarjo. The research method used is R&D from the Alessi and Trollip model. Data collection using a google form-based questionnaire filled out online and test results. The data were analyzed by qualitative descriptive and percentage calculation. The results obtained: (1) the value of the validity of the material questions is 90%, (2) the value of media validity is 94%, and (3) the student implementation test score is 81.75%.